Analysis of climate variability and its impact on drought phenomenon in Karadag district using SPI and SPEI criteria (A Study in Environmental Geography) - Mohammed, Kurdistan Kamal; Amin, Prof.Dr. Hawre Yasin Mohammed (Sulaimani Journal for Humanities, 2026)
This study focuses on analyzing the phenomenon of climatic variability and its impact on the development of drought in the Qaradagh region, as climatic drought and its effects on the natural environment of the Kurdistan Region have become a critical subject of research due to its direct correlation with economic, hydrological, and agricultural sectors, as well as food security and livelihoods. The primary objective of this research is to determine the magnitude and nature of climatic shifts within the study area, specifically regarding precipitation and temperature elements, and to identify the factors responsible for climatic variability and deviation, assessing their influence on the emergence, classification, and severity of drought in the region. To achieve the study's objectives, climatic data from the Sulaymaniyah station for a twenty-year period (2004–2023) were utilized, and the research is structured into four main sections, where the first section examines the characteristics of the study area, the second analyzes the climatic characteristics of the region, the third investigates climatic deviation and variability, and the fourth focuses on identifying drought phenomena through both the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI), The methodology employs a descriptive approach to characterize the study area and its natural environment, and a quantitative analytical approach through statistical equations to measure the extent of variability and deviation from the normal means of temperature and rainfall, followed by a comparative method to contrast the variability rates between two climatic cycles and correlate them with the trends of drought emergence using the SPI and SPEI indicators. Following a detailed data analysis, the study concluded that climatic variability is a defining characteristic of the study area, despite differences in variability trends between the two climatic cycles, classifying the region's climatic variability as highly severe. These fluctuations in temperature and rainfall have significantly influenced the onset of drought, and the SPI and SPEI results demonstrate that the Qaradagh district has undergone multiple drought cycles during the study period, where dry years are directly linked to negative precipitation deviations and positive temperature deviations, identifying ten years of drought with varying intensities, most notably the 2021–2022 period, which was classified as a year of Extreme drought
Keywords: Environmental problems; climate change; drought; mean deviation; temperature and rainfall; SPI; SPEI